Religious Perspective of Funeral Care Accountability and Sustainability - Nurul Mukhlisah; Lea Emilia Farida; Sirajudin (Yayasan Rumah Peneleh, 2022)
This study aims to reveal accountability and sustainability in religious activities, relating to funeral service at Al Jihad Mosque in Banjarmasin. The activity has been going on for a long time and necessitates accountability and sustainability in the activities of mutual assistance in the mourning conditions. This study uses a qualitative approach with the technique of indexing the results of interviews from informants and analyzing the contextual accountability and sustainability of funeral service at Al Jihad Mosque. The result reveals that Al Jihad Mosque has a funeral service unit that provides services without any direct financial ties like the other dues of funeral's aid model in general. They are more open with accountability of the costs required to administer the funeral service and focus on professionalism in services provision.